2019
DOI: 10.1111/vco.12469
|View full text |Cite
|
Sign up to set email alerts
|

Nectin‐4 and p63 immunohistochemical expression in canine prostate tumourigenesis

Abstract: Nectin‐4 is an E‐cadherin‐based adherens junction protein of normal epithelial cells, as well as a potent mediator of anchorage‐independent cancer colony formation. It is considered a tumour‐associated histological and serological marker in various human cancers. The transcription factor p63 is a basal cell marker in the normal prostate, involved in cell adhesion, as well as in the formation and survival of circulating tumour cell clusters. The aim of this study was to evaluate Nectin‐4 and p63 immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(88 reference statements)
3
9
1
Order By: Relevance
“…The results of HE staining and IHC experiments showed that the canine mammary tumours, especially invasive breast cancers, had different cell sizes and a large degree of atypia, and lower ERα‐ and p63‐positive rates and higher Ki67‐ and HK2‐positive rates were found in the CMT samples compared to control samples (Figure 1). Altogether, these data suggest that the epidemiological and pathological features of CMTs are similar to previous studies about CMT 1,28 …”
Section: Resultssupporting
confidence: 88%
“…The results of HE staining and IHC experiments showed that the canine mammary tumours, especially invasive breast cancers, had different cell sizes and a large degree of atypia, and lower ERα‐ and p63‐positive rates and higher Ki67‐ and HK2‐positive rates were found in the CMT samples compared to control samples (Figure 1). Altogether, these data suggest that the epidemiological and pathological features of CMTs are similar to previous studies about CMT 1,28 …”
Section: Resultssupporting
confidence: 88%
“…In the few available canine studies which evaluated p63 in PCa, the tumours were characterized by rare or absent expression of p63, 19–21 with the exception of a very rare subtype of glandular PCa, which aberrantly expresses p63 21 . In the canine cases of the present study, p63 expression was limited to rare (<5%) cells in most (90%) PCa, which is in agreement with previous studies 20 . The remaining four cases, consisting of two PCa with squamous differentiation and two well differentiated, suspected UC, were characterized by strong expression of p63.…”
Section: Discussionsupporting
confidence: 91%
“…In benign, that is, normal as well as hyperplastic, canine prostates examined in the present study, basal cell staining confirmed the previously reported discontinuous basal cell layer in dogs 18–20 . In contrast to p63 and CK5/6, IHC for CK14 revealed only rare staining of basal cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations